2020
DOI: 10.3389/fimmu.2020.00790
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Dietary N-Glycans From Bovine Lactoferrin on Toll-Like Receptor 8; Comparing Efficacy With Chloroquine

Abstract: Toll-like receptor 8 (TLR-8) plays a role in the pathogenesis of autoimmune disorders and associated gastrointestinal symptoms that reduce quality of life of patients. Dietary interventions are becoming more accepted as mean to manage onset, progression, and treatment of a broad spectrum of inflammatory conditions. In this study, we assessed the impact of N-glycans derived from bovine lactoferrin (bLF) on the inhibition of TLR-8 activation. We investigated the effects of N-glycans in their native form, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, the fermentation of milk and/or LF by gut microbiota releases many active compounds (Cockburn & Koropatkin, 2016) that may directly interact with the viral particles and/or modulate the immune response. In a recent study (Figueroa-Lozano et al, 2020), scanned the effects of N-glycans derived from bovine LF on monocyte-derived dendritic cells. This study revealed that although TLR-2, TLR-5, TLR-7, and TLR-9 were not significantly altered, the different isolated N-glycan forms from bLF possessed a tight regulation of TLR-3, TLR-4, and TLR-8, as well as increased the IL-6 production (Figueroa-Lozano et al, 2018).…”
Section: Viral Neutralization (Extracellular Inhibition)mentioning
confidence: 99%
“…Furthermore, the fermentation of milk and/or LF by gut microbiota releases many active compounds (Cockburn & Koropatkin, 2016) that may directly interact with the viral particles and/or modulate the immune response. In a recent study (Figueroa-Lozano et al, 2020), scanned the effects of N-glycans derived from bovine LF on monocyte-derived dendritic cells. This study revealed that although TLR-2, TLR-5, TLR-7, and TLR-9 were not significantly altered, the different isolated N-glycan forms from bLF possessed a tight regulation of TLR-3, TLR-4, and TLR-8, as well as increased the IL-6 production (Figueroa-Lozano et al, 2018).…”
Section: Viral Neutralization (Extracellular Inhibition)mentioning
confidence: 99%
“…Such binding has been reported for Gram-negative bacterial lipopolysaccharide (LPS) [ 20 ]. The mechanisms of the interaction of lactoferrin with various receptors are strongly linked to its glycan conformation; it has been observed that there is an interaction between some TLRs and Lf, mediated by glycans of the molecule, allowing an immunomodulatory effect [ 21 , 22 ]. Lf also plays a role in the differentiation, maturation, activation, migration, proliferation, and function of cells belonging to antigen-presenting cells (APCs), such as B cells, neutrophils, monocytes/macrophages, and dendritic cells [ 23 , 24 ].…”
Section: Immunomodulatory and Anti-inflammatory Activitymentioning
confidence: 99%
“…Activation of the IFN-β transcripts following Lf incubation, not direct viral binding, was recently found to be the mechanism behind anti-norovirus activity [ 96 ]. N-glycans isolated from bovine lactoferrin (bLf) has been demonstrated to lower TLR-8 activation, through interaction with the N-glycans on its dimer, the inhibitory effect was demonstrated to be as effective as chloroquine, a commonly prescribed anti-malaria and autoimmune drug [ 97 ]. In view of these anti-viral activities through immune modulation, Lf has also been investigated for use as a vaccine adjuvant.…”
Section: Ingredients Inspired By Human Milkmentioning
confidence: 99%